2018
DOI: 10.1042/bst20180145
|View full text |Cite
|
Sign up to set email alerts
|

ABCG2: does resolving its structure elucidate the mechanism?

Abstract: ABCG2 is one of a few human membrane transporters which display the amazing ability to transport multiple different chemicals out of cells. These multidrug pumps, which have orthologues in all organisms, are important in humans in the context of drug pharmacokinetics, especially with respect to resistance to chemotherapy. In 2016, we presented a mini-review on ABCG2 which identified many areas of exciting research progress as well as many areas of frustrating ignorance. Just 2 years on the field has advanced, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 62 publications
0
14
0
Order By: Relevance
“…ABCG2 is also crucial in the pharmacokinetics of several compounds [1][2][3] which is highlighted by the fact that the US Food and Drug Administration and the European Medicines Agency list ABCG2 among the transporters to be investigated for pharmacokinetics and drug-drug interactions [4,5]. Experimental data showed that ABCG2 can handle substrates with a wide variety in size and polarity [2,6,7]. Uric acid is a small and amphiphilic physiological substrate [8,9], Hoechts 33342 [10] is a large hydrophobic molecule, and methotrexate [11] or various sulfated and glucuronide conjugates [12] are more polar substrates.…”
Section: Introductionmentioning
confidence: 99%
“…ABCG2 is also crucial in the pharmacokinetics of several compounds [1][2][3] which is highlighted by the fact that the US Food and Drug Administration and the European Medicines Agency list ABCG2 among the transporters to be investigated for pharmacokinetics and drug-drug interactions [4,5]. Experimental data showed that ABCG2 can handle substrates with a wide variety in size and polarity [2,6,7]. Uric acid is a small and amphiphilic physiological substrate [8,9], Hoechts 33342 [10] is a large hydrophobic molecule, and methotrexate [11] or various sulfated and glucuronide conjugates [12] are more polar substrates.…”
Section: Introductionmentioning
confidence: 99%
“…Structural data on the ABCG family have brought us considerably further forwards in understanding the mechanism of these half-transporters [18,23]. Until there were structural data, the region between the NBD of ABCGs and the first transmembrane (TM) helix (over 150 residues in total, e.g., from ca.…”
Section: Discussionmentioning
confidence: 99%
“…These structures have revealed that ABCG2 has an internal cavity for drug substrate and inhibitors that is connected to an external cavity and that the propulsion of bound substrates from one cavity to the other is likely to form the basis for transmembrane transport [19][20][21]23]. The structures have already provided the foundation for understanding numerous studies that have identified specific residues of importance in contributing towards drug specificity and inter-domain communication [24][25][26], and will continue to help understand how drug binding and transport is coupled to nucleotide binding and hydrolysis [27].…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, the fungal NBD1 has three minor differences, in that (i) a glutamine residue in the Q-loop is replaced with glutamate, (ii) the histidine residue in the H-loop is substituted with tyrosine and (iii) the Pro-loop is missing but contains a glycine instead [ 337 ] ( Table 4 ). The non-identical deviant NBDs in fungal PDRs [ 41 , 216 , 338 , 339 ] may support an asymmetric catalytic cycle as proposed for ABCG5/G8 [ 38 , 339 , 340 , 341 ], whereas “symmetric” cycles require the presence of fully conserved “canonical” ATP-binding sites in both NBDs.…”
Section: C Albicans Pdr/cdr1 Holds All Conserved Motifs Critical For Abcg Functionmentioning
confidence: 99%